Why Performance Management Should Not Be Like Dieting*. Issue 4 (11th February 2017) - Blackman, Deborah; Buick, Fiona; O'Donnell, Michael
Abstract: Globally, organisations have long been preoccupied with using employee performance management to enhance organisational performance. However, due to the compliance‐based way in which it is often implemented, success has been limited. This paper proposes lessons can be learnt from adopting the analogy of 'dieting'. Short‐term weight‐loss practices can lead to a cyclical pattern that generates weight gain, rather than loss, in longer term. This occurs due to dieters following fads focused on short‐term loss, rather than habitual modifications necessary for long‐term weight change. This may explain why despite organisations pursuing the perfect employee performance management system (akin to dieting fads), they remain ineffective. We argue that compliance‐based approaches encourage a short‐term focus on completing the process (known pejoratively as 'tick‐and‐flick'). However, where performance management is considered core business, more sustainable practices emerge. Similar to weight loss, these represent the habitual modifications necessary for enabling high performance over the longer term. Abstract : Dieters following fads focus on short‐term loss, rather than habitual modifications necessary for long‐term weight change. This might explain why despite organisations pursuing perfect employee performance management systems (akin to dieting fads), they remain ineffective. We argue that when performance management is core business, sustainable practices emerge that enable high performance.